2000
DOI: 10.1038/81881
|View full text |Cite
|
Sign up to set email alerts
|

Early sleep triggers memory for early visual discrimination skills

Abstract: Improvement after practicing visual texture discrimination does not occur until several hours after practice has ended. We show that this improvement strongly depends on sleep. To specify the process responsible for sleep-related improvement, we compared the effects of 'early' and 'late' sleep, dominated respectively by slow-wave and rapid eye movement (REM) sleep. Discrimination skills significantly improved over early sleep, improved even more over a whole night's sleep, but did not improve after late sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
302
3
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 467 publications
(337 citation statements)
references
References 35 publications
(50 reference statements)
23
302
3
2
Order By: Relevance
“…Finally, alternative interpretations suggest that the consolidation of memory traces during post-training sleep would require the succession of non-REM and REM sleep episodes (Giuditta et al, 1995;Gais et al, 2000;Stickgold et al, 2000). The present data can neither confirm or infirm these hypotheses.…”
Section: Functional Relationships Between Rem Sleep and The Processincontrasting
confidence: 82%
“…Finally, alternative interpretations suggest that the consolidation of memory traces during post-training sleep would require the succession of non-REM and REM sleep episodes (Giuditta et al, 1995;Gais et al, 2000;Stickgold et al, 2000). The present data can neither confirm or infirm these hypotheses.…”
Section: Functional Relationships Between Rem Sleep and The Processincontrasting
confidence: 82%
“…It absolutely requires sleep [12,13]. This unequivocal establishment of a specific vision-related activity that requires sleep lends strong support to the foregoing proposals for the role of detailed focal vision in sleep's origin.…”
Section: Consolidating Visual Discriminations Requires Rem and Nrem Ssupporting
confidence: 62%
“…Sleep-dependent memory improvement in hippocampalrelated tasks appears to be reliant on SWS (Gais et al 2000). In particular, Gais and Born have demonstrated that low acetylcholine during SWS is important for explicit verbal memory (Gais et al 2004), but not implicit memory.…”
Section: Resultsmentioning
confidence: 99%